Demographic Influences on Why Academic Self-Initiated Expatriates Work in Saudi Universities - شريفة عبد الله الغامدي (Faculty of Education - Port Said University, 2020)
In today's global economy, the continuing expansion of international trade and the need for specialized expertise have demanded an increase in the expatriates moving abroad for work in the private and public sectors of developing economies. This article aims to understand the self-initiated expatriation (SIE) experience by examining the influence of demographics on SIE reasons to work in Saudi Universities. Quantitative survey data were obtained from 300 respondents, who were academic SIEs employed at Saudi Universities. An analysis identified a statistically significant difference in SIEs' reasons to relocate across the demographic variables of language, nationality, and seniority. Gender and previous experience were not significant differentiators. There are gaps in the extant expatriation literature on academic SIEs living and working in host developing countries (HDCs). Understanding the impact of demographics on SIEs' motives helps human resource managers develop improved strategies for recruitment, performance, and retention of academic SIEs and retention of academic SIEs